Mechanical and Vibrational Analysis of Chicken Feather Hybrid Composites - RAMANATHAN, Chennakeshava; SHIVAKUMAR, Supreeth; VANAROTTI, Mohan B.; SIDDAPPA, Puttaswamaiah (Engineering Transactions, 2025)
Due to significant advancements in composites across various fields of engineering, the selection of materials (fibers and/or matrix) for manufacturing composites for specific and/or required applications has become increasingly important nowadays. The use of natural fibres, which possess good mechanical properties, is gaining attention as they can mitigate the environmental harm caused by artificial fibers. One notable natural fiber is chicken feather fiber (CFF), a waste by-product that poses a significant disposal problem. In this study, CFFs were employed to fabricate lightweight composites using hand-layup process and were tested according to ASTM standards for tensile, flexural, and vibrational properties. The extracted CFF were combined with glass fibers in varying weight ratios – 0%, 10%, and 20% – to fabricate a hybrid composite material. Frequency response tests conducted using a fast Fourier transform (FFT) analyzer provided the natural frequency and different mode shapes of all composite samples. Furthermore, finite element analysis (FEA) simulations of all hybrid composite (HC) specimens was simulated in ANSYS, and the results were compared with experimental values.